2008
DOI: 10.1111/j.1083-6101.2008.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Global Youth: Mobile Gaming in the U.S., Spain, and the Czech Republic

Abstract: Capturing Global Youth: Mobile Gaming in the U.S., Spain, and the Czech RepublicWe adapt the technology acceptance model (TAM) to examine the factors influencing mobile gaming adoption among ''global youth.'' Our model replaces usefulness with convenience, incorporating visual appeal and escapism as antecedents of fun, and perceived novelty and economic value as antecedents of convenience. Questionnaire surveys were conducted in the U.S., Spain, and the Czech Republic, producing 432 usable responses. In the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 44 publications
1
23
0
1
Order By: Relevance
“…This could be explained by "westernization" of the global society; Internet and mobile gadgets are viewed internationally by many young people as a "nice thing to have". A large international survey of young people in the US, Spain and Czech Republic [21] found that ubiquity of mobile devices had a greater effect on mobile game adoption than the perceived fun: young people clearly prefer the convenience to play a game at any time and any place using a small device that they carry around with them. Consistently across the countries, young people indicated that they prefer such a form of entertainment because it allows them to find something enjoyable to do when otherwise they would have been bored and forced to do nothing.…”
Section: What About Mobile Culture?mentioning
confidence: 99%
“…This could be explained by "westernization" of the global society; Internet and mobile gadgets are viewed internationally by many young people as a "nice thing to have". A large international survey of young people in the US, Spain and Czech Republic [21] found that ubiquity of mobile devices had a greater effect on mobile game adoption than the perceived fun: young people clearly prefer the convenience to play a game at any time and any place using a small device that they carry around with them. Consistently across the countries, young people indicated that they prefer such a form of entertainment because it allows them to find something enjoyable to do when otherwise they would have been bored and forced to do nothing.…”
Section: What About Mobile Culture?mentioning
confidence: 99%
“…The extent to which one perceives poor quality to inhibit him/her to use 3G (Okazaki et al, 2008), or emotional value in western literature, as they all refer to the perceived pleasure derived from using the innovation. In traditional Chinese cultural values, "face" is a concept of central importance.…”
Section: Concept Definitionmentioning
confidence: 99%
“…Their study found that Italians had a more negative perception of computer games and as a result performed poorly compared with the American subjects. The need for culture-specific gaming has been further explored by Okazaki et al (2008) on a study of American, Czech, and Spanish adoption of mobile gaming. The researchers found culture-specific trends in mobile gaming needs and habits with respect to age, technological learning capacity, and gender.…”
Section: Gamer Experiencementioning
confidence: 99%
“…The researchers found culture-specific trends in mobile gaming needs and habits with respect to age, technological learning capacity, and gender. The study reported on the varied popularity of mobile gaming regardless of culture (Brogden & Williams, 1996;Chan, Frydenberg, & Lee, 2007;Constantiou, Papazafeiropoulou, & Vendelo, 2009;Ganesh, Kumar, & Subramaniam, 1997;Marks, 1991;Okazaki et al, 2008;Rayboum, 1997;Rosen & Weil, 1995;Woolnough et al, 1997). Zhang et al (2009) carried out a cross-cultural experiment to test if video gaming experience developed problem-solving skills in both experienced and inexperienced game players across American and Chinese players.…”
Section: Gamer Experiencementioning
confidence: 99%